Factors Associated with Affective Symptoms and Quality of Life in Patients with Atopic Dermatitis - Silvia Mariel Ferrucci; Simona Tavecchio; Luisa Angileri; Teresa Surace; Emilio Berti; Massimiliano Buoli (Medical Journals Sweden, 2021)
The aim of this study was to detect demographic and clinical factors associated with affective symptoms and quality of life in patients with severe atopic dermatitis. First, one-way analyses of variance and correlations were performed to compare a large set of qualitative and quantitative clinical variables. Three final multivariable regression models were performed, with depression/anxiety subscales and Dermatology Life Quality Index scores as dependent variables, and the factors that were statistically significant on univariate analyses as independent ones. More severe anxiety symptoms and poorer quality of life (p < 0.01) were significantly associated with more severe depressive symptoms. Female sex and disturbed sleep (p = 0.03) were significantly associated with more severe anxiety. Finally, previous treatment with cyclosporine (p = 0.03) or methotrexate (p = 0.04), more severe depressive symptoms (p < 0.01), itch (p = 0.03), impaired sleep (p < 0.01) and perceived severity of dermatological illness (p < 0.01) were significant predictors of low quality of life. This study shows a complex interplay between the severity of atopic dermatitis, poor quality of life and presence of clinically relevant affective symptoms. These results will help dermatologists to identify patients who need psychiatric consultation within the framework of a multidisciplinary approach.